(untitled) - Souza, Selma Rodrigues de (2024)
This research addresses the significant transformations and adaptations required of educators in the context of contemporary higher education. The central guiding question of the study is: What fundamental attitude changes are necessary for university professors to deliver effective teaching in response to societal demands? The general objective is to analyze the possible attitude changes among higher education faculty in light of the transformations brought about by the Knowledge and Information Society, while promoting updates in pedagogical approaches and teaching-learning relationships. The research employs a qualitative methodology, utilizing a literature review and content analysis, drawing on the works of authors such as Castells (1996), Gaeta (2007), Gaeta and Masetto (2022), Hargreaves (2004), Jarvis (2000, 2007), Masetto (2000, 2012, 2015, 2018), Pozo (2007, 2002), and Masetto and Behrens (2000). The findings indicate that attitude changes are essential for university professors to effectively navigate rapid social and educational transformations, highlighting the importance of adopting innovative pedagogical models and redefining the roles of both teachers and students as co-protagonists in the teaching-learning process. These changes are vital for fostering curricular innovations and equipping students to meet the challenges of the 21st century.